Efektifitas Sanksi Pidana Dalam Pasal 8 Peraturan Walikota Jambi Nomor 21 Tahun 2020 Dalam Pelanggaran Penerapan Protokol Kesehatan Di Kota Jambi - Reza Iswanto (Wajah Hukum, 2021)
This research describes the effectiveness of criminal sanctions in Article 8 of Jambi Mayor Regulation Number 21 of 2020 in violating the application of health protocols in Jambi City, the factors that affect the effectiveness of criminal sanctions in Article 8 of Jambi Mayor Regulation Number 21 of 2020 in violating the application of health protocols in Jambi City. Jambi City and efforts to streamline criminal sanctions in Article 8 of Jambi Mayor's Regulation Number 21 of 2020 for violating the application of health protocols in Jambi City. The research method used in this research is juridical empirical so that this research is more descriptive in nature, the data sources are primary and secondary sources, the research approach is a case approach, the data collection technique in this research is document study and the data analysis in this research is carried out qualitatively. . The results of the study show that the Jambi City government and the people of Jambi City have not implemented criminal sanctions in Article 8 of Jambi Mayor Regulation Number 21 of 2020, there are Jambi City people who do not use masks when they are outside the home, as for the factors that influence it, namely law enforcement and community factors. so that the efforts made, namely the Jambi City government must instill legal awareness of the people of Jambi City by making effective criminal sanctions fines in Article 8 of Jambi Mayor's Regulation Number 21 of 2020.